RESILIENSI KELUARGA TERHADAP KESEHATAN MENTAL MAHASISWA UINSYARIF HIDAYATULLAH JAKARTA - Salsa Nur Haliza; Nasichah, Laila Afifah, Nur Aisah, Ramdan Wahid (CV. ADIBA AISHA AMIRA, 2024)
This research discusses family resilience towards student mental health, focusing on the role of the family in maintaining the psychological well-being of adolescents. The family is one of the closest areas, there are many cases regarding mental health, so this research aims to examine and observe the role of the family in the mental health of their children. The method used is correlational or the method used to determine whether or not there is a relationship between two variables. In this research, data was collected using a Google form, a questionnaire distributed to students at UIN Syarif Hidayatullah Jakarta and voting with participants who were teenagers who were growing up aged around 18 up to 24 years. The participants certainly have different backgrounds ranging from culture, education, family, economics and religion. The results of the research show that the role of the family is very important for the mental health of family members, especially children. From this research we know what role parents should play in maintaining their child's mental health.